THE ROLE OF GENETIC FACTORS IN THE TREATMENT TACTICS OF DUODENAL ULCERS COMPLICATED BY BLEEDING - Oktyabr R. Teshaev; Olim R. Mavlyanov; Suxrob U. Alimov (Central Asian Journal of Medicine, 2023)
In the etiology of peptic ulcer, hereditary burden plays a certain role. Therefore, when studying the nature of hereditary predisposition to gastric ulcer (GU) and duodenal ulcer (DU), an important direction is the identification of genetic markers. In order to fulfill the tasks set in accordance with the purpose of the research, 725 patients with duodenal ulcer disease complicated with bleeding. In our research, the relationship between body composition and clinical and laboratory indicators of bleeding was determined in the examination of patients with a complicated course of duodenal ulcer disease according to the most important clinical signs. Thus, in patients with duodenal ulcer disease complicated by bleeding, it was possible to choose treatment methods, size and type of surgery, taking into account the peculiarities of the constitutional body structure.